Dynamic and Meta-Context Switching for Gaze-Based Interaction - Diaz-Tula, Antonio; H. Morimoto, Carlos (Journal on Interactive Systems, 2015)
In this paper we investigate the performance of a gaze-based interaction system that combines Dynamic Context Switching and Meta-Context Switching. These methods are extensions of the Context Switching interaction paradigm. The original context switching idea uses fixed-size contexts. Each context carries the same information, so the user can browse freely within a context without worrying about the Midas touch problem. A saccade to the other context triggers the selection of the item under focus. Dynamic context switching dynamically adjusts the size of a context to improve its useful area, where the context that has the user focus is displayed in full size and the other is minimized. Meta-context switching uses meta-keys to allow the user to escape from the current task and select other contexts or change the operation mode. We have designed and conducted two user experiments to evaluate these new gaze interaction techniques and compare them with selection by dwell time in a search task. The task required browsing through several pages using meta-keys. The experimental results show that dynamic context switching improves user performance when compared to fixed-size context switching and do not cause disorientation. The error rate was significantly higher for dwell time due to the Midas touch problem, although the time spent to complete the task was similar for dwell time and dynamic context switching.